Efektivitas E-modul Pendidikan Pancasila pada materi NKRI berbasis aplikasi Heyzine Flipbook dalam Meningkatan Hasil Belajar Siswa - Untari, Aryanti Dwi; Khoirunnisa, Dira (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2025)
This study aims to determine the effectiveness of the Pancasila education e-module on the material of the Unitary State of the Republic of Indonesia (NKRI) based on the Heyzine Flipbook application in improving the learning outcomes of class X DKV 1 students of SMKN 3 Kota Serang. The development of e-modules plays an important role in supporting learning success, therefore the Heyzine Flipbook application-based e-module is the right e-module to improve student learning outcomes. The research method used is Research and Development (R&D) with the ADDIE model consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques in this study include analysis sheets, validation sheets, student and teacher response questionnaires, practice tests, and learning outcome tests. The analysis techniques used are qualitative descriptive analysis and quantitative descriptive analysis. Based on the results of this study, it shows that the Pancasila education e-module on the NKRI material based on the Heyzine Flipbook application is effective in improving the learning outcomes of class X DKV 1 students of SMKN 3 Kota Serang by obtaining a classical completion score of 80% on the test questions.